Changes in morphological and physiological parameters affecting lettuce cultivars due to nitrogen fertilizer in greenhouse tunnel - R him, Thouraya; Romdhane, Leila; Nicoletto, Carlo; Tlili, Imen; Ilahy, Riadh (Journal of Postharvest Technology, 2024)
Lettuce (Lactuca sativa L.) is one of the most widely grown leafy vegetable in the world. It is appreciated for its balanced nutritional value and its dietary properties. Nitrogen nutrition is a key factor in controlling Lettuce (Lactuca sativa L.) production. The lettuce types Romaine, Iceberg, Batavia type and Butterhead treated with the nitrogen levels: control (N0), 40 kg∙ha-1 N (N40), 60 kg∙ha-1 N (N60), 80 kg∙ha-1 N (N80) and 120 kg∙ha-1 N (N120) in a 3 year experiment. Yield, growth and qualitative parameters of the plant were measured. The Romaine and the Iceberg types produced a high exploratory potential of the root system, intercepting more nutrients and resulting in a higher growth rate. The Iceberg type differed from the others by growth speed compared to foliar initiation speed. The higher accumulation of dry matter per day affirms that this type tends to be more efficient than others in use of resources. The N60 seems to be suitable under conditions of the test with acceptable production and induces a lower sensitivity of the crop to Bremia diseases. The N80 dose produced a higher yield, and reduced damage from Bremia compared to 120 kg∙ha-1 N. The Iceberg type was the most efficient in dry matter production particularly under the dose of 80 kg ha-1. Concerning lettuce quality, it has been shown that residual nitrate content was incompliance with the European regulation in all type of lettuce disregarding the applied nitrogen dose.